European financial law and the state-finance nexus: Sovereign privileges or market discipline for safe public debt? - Ad van Riet (Finance and Society, 2023)
European financial regulation consistently gives governments privileged access to private investors, reflecting the anchor role assigned to sovereign securities as safe and liquid assets for the financial system. Legislative reforms after the financial crisis of 2008 further expanded the preferential treatment of sovereign securities as zero-risk claims, introduced portfolio requirements in favour of public debt, and constrained market speculation against governments. These sovereign privileges appear counterproductive for fiscal discipline and financial stability: they encourage excessive public debt issuance and make financial institutions holding government bonds - in particular from euro area countries with a variable risk profile - vulnerable to fiscal turbulence. Governments seem to have a conflict of interest. On the one hand, they are prudential regulators of financial risk-taking, on the other hand, they tend to overlook the financial sector's exposure to sovereign risk. This article considers four theories of the state-finance nexus and their solutions to this conflict of interest. The money view, the franchise view, and the modern financial repression view draw on the state's monetary and regulatory powers over finance to confirm sovereign safety. Their positions fundamentally contrast with the neoliberal view, which relies on free markets to enforce sustainable public finances. The article concludes that sovereign privileges present a fundamental dilemma for European financial governance with a neoliberal orientation: they oblige private investors to hold public debt, while weakening the role of markets in promoting fiscal discipline as the very foundation of sovereign safety.
Keywords: 300; European law; financial governance; sovereign privilege; sovereign safety; state-finance nexus